The Value of Applying Ethical Principles in Telehealth Practices: Systematic Review - Keenan, Amanda Jane; Tsourtos, George; Tieman, Jennifer (JMIR Publications, 2021)
BackgroundAs the use of technology to deliver health services is increasing rapidly and has further intensified during the COVID-19 pandemic, these initiatives may fail if ethical impacts are not fully identified and acted upon by practitioners. Ignoring the ethical impacts of information and communication technology health service delivery creates an unintended risk for patients and can lead to reduced effectiveness, noncompliance, and harm, undermining the best intentions of governments and clinicians. ObjectiveOur aim was to explore how ethical considerations or impacts may be different, greater, or more variable in information and communication technology methods versus face-to-face health care delivery models, and how they may be applied in practice. MethodsWe undertook a systemic literature review to provide a critical overview of existing research into the incorporation of ethical principles into telehealth practice. Six databases were searched between March 2016 to May 2016 and again in December 2020 to provide the benefit of currency. A combination of broad terms ("ethics," "ethical," "health," and "care") with the restrictive terms of "telehealth" and "telemedicine" was used in keyword searches. Thematic analysis and synthesis of each paper was conducted, aligned to the framework developed by Beauchamp and Childress. ResultsFrom the 49 papers reviewed, authors identified or discussed the following ethical principles in relation to telehealth practice: autonomy (69% of authors, 34/49), professional-patient relationship (53% of authors, 26/49), nonmaleficence (41% of authors, 20/49), beneficence (39%, of authors, 19/49), and justice (39% of authors, 19/49). ConclusionsAlthough a small number of studies identified ethical issues associated with telehealth practice and discussed their potential impact on service quality and effectiveness, there is limited research on how ethical principles are incorporated into clinical practice. Several studies proposed frameworks, codes of conduct, or guidelines, but there was little discussion or evidence of how these recommendations are being used to improve ethical telehealth practice.